The acceptability and feasibility of using the Adult Social Care Outcomes Toolkit (ASCOT) to inform practice in care homes. Issue 1 (December 2016) - Towers, Ann-Marie; Smith, Nick; Palmer, Sinead; Welch, Elizabeth; Netten, Ann
Abstract Background The Adult Social Care Outcomes Toolkit (ASCOT) measures social care related quality of life (SCRQoL) and can be used to measure outcomes and demonstrate impact across different social care settings. This exploratory study built on previous work by collecting new inter-rater reliability data on the mixed-methods version of the toolkit and exploring how it might be used to inform practice in four case study homes. Method We worked with two care home providers to agree an in-depth study collecting SCRQoL data in four case-study homes. Data was collected about residents' age, ethnicity, cognitive impairment, ability to perform activities of daily living and SCRQoL in the four homes. Feedback sessions with staff and managers were held in the homes two weeks after baseline and follow-up data collected three months later. Interviews with managers explored their views of the feedback and recorded any changes that had been made because of it. Results Participant recruitment was challenging, despite working in partnership with the homes. Resident response rates ranged from 23 to 54 % with 58 residents from four care homes taking part in the research. 53 % lacked capacity to consent. Inter-rater reliability for the ASCOT ratings of SCRQoL were good at time one (IRR = 0.72) and excellent at time two (IRR = 0.76). During the study, residents' ability to perform activities of daily living declined significantly (z = -2.67, p < .01), as did their expected needs in the absence of services (z = -2.41, p < .05). Despite these rapid declines in functionings, residents' current SCRQoL declined slightly but not significantly (Z = -1.49, p = .14). Staff responded positively to the feedback given and managers reported implementing changes in practice because of it. Conclusion This exploratory study faced many challenges in the recruitment of residents, many of whom were cognitively impaired. Nevertheless, without a mixed-methods approach many of the residents living in the care homes would have been excluded from the research altogether or had their views represented only by a representative or proxy. The value of the mixed-methods toolkit and its potential for use by providers is discussed.